Creating a conservation network: Restoration of the critically endangered Chinese crested tern using social attraction. (August 2020) - Lu, Yiwei; Roby, Daniel D.; Fan, Zhongyong; Chan, Simba; Lyons, Donald E.; Hong, Chung-Hang; Wang, Siyu; Yang, Jia; Zhou, Xiao; Chen, Dongdong; Yuan, Hsiao-Wei; Chen, Shuihua
Abstract: Social attraction techniques have been demonstrated effective in restoring seabird breeding colonies, especially colonies of terns (Subfamily: Sterninae). The Chinese crested tern ( Thalasseus bernsteini ) is a critically endangered seabird with a global population of about 100 breeding adults and a breeding range restricted to the East China Sea and the Yellow Sea. In order to restore a breeding colony of Chinese crested terns in an archipelago where a former colony had been abandoned, social attraction (decoys and audio playback systems) was deployed on a small, uninhabited island with no history of seabird nesting. The objective was to establish a breeding colony of greater crested terns ( T. bergii ), a closely-related common species, in the hope that Chinese crested terns would follow. Thousands of greater crested terns and at least 19 Chinese crested terns colonized the island during the first breeding season after deployment of social attraction. After three years of successful breeding, the colony was abruptly abandoned early in the fourth breeding season because of invasive king rat snakes ( Elaphe carinata ), which consumed all tern eggs. Following removal of all snakes from the colony, terns resumed nesting the subsequent year. Recovery of this critically endangered seabird depends on repeating this process at multiple islands. Careful planning, in conjunction with habitat management, close colony monitoring, and deployment of social attraction, can establish a conservation network of suitable, secure colony sites where most breeding adults can reproduce successfully. This approach can be used to restore a variety of declining seabird species along the Chinese coastline.